Unannounced interim inspections: do false alarms matter? - Avenhaus, Rudolf; Krieger, Thomas (Mathematical Modelling and Analysis, 2011)
Unannounced Interim Inspections (UIIs) in nuclear facilities of the European Union have recently attracted major attention by the International Atomic Energy Agency (IAEA) and by European Atomic Energy Community (EURATOM)in the context of the IAEA/EURATOM Partnership Approach. Therefore, a research project had been organized by the Joint Research Centre in Ispra in collaboration with the Universität der Bundeswehr München in the framework of which the assumptions have been classified which are necessary for a quantitative analysis and a few variants have been studied in detail. In that project only so-called Attribute Sampling Procedures were considered which means that only errors of the second kind (no detection of the illegal activity), but not those of the first kind (false alarms), where taken into account. It was the purpose of the work presented here to investigate the impact of errors of the first kind on UIIs which may occur if so-called Variable Sampling Procedures are used. Two kinds of planning UIIs are considered: in the sequential one both players, the inspector and the operator of the facility, decide step by step to inspect resp. to start the illegal activity – if there is one. In the hybrid-sequential one the inspector decides at the beginning of the reference time interval where to place his UIIs, whereas the operator acts again sequentially. For two UIIs during the reference time interval equilibria are determined, which generalize the results of the above mentioned research project. It turns out that in both cases, the sequential and hybrid-sequential one, the equilibrium strategies of the inspector and the equilibrium payoffs to both players are the same, but not the equilibrium strategies of the operator. We try to present a plausible explanation for this surprising result.